Unsafe abortion in Brazil: a systematic review. (30th September 2020) - Domingues, R; Fonseca, S; Leal, M; Aquino, E; Menezes, G
Abstract: Background: In Brazil, abortion is legally allowed in cases of risk to the woman's life, pregnancy resulting from rape and cases of fetal anencephaly. Despite the restrictive legislation, studies estimated that around 1 million abortions took place in the country in 2005. Abortions occurred regardless of womeńs socioeconomic position, race, age and religion, but unsafe practices were more common among young women, with low educational levels, single, students or domestic workers. This study sought to update knowledge on unsafe abortion in Brazil. Methods: We carried out a systematic review with study search on Medline and LILACS, with no language restriction, from 2008 to 2018. We evaluated article quality using the Joanna Briggs Institute instruments. We evaluated 50 articles. Results: There was a decrease in the ratio of induced abortions by 1, 000 women of reproductive age reaching 16 per 1, 000 in 2013. However, direct estimates do not indicate a decrease in the prevalence of induced abortion, estimated to be 13% in 2016. Higher prevalences were observed in more socially vulnerable populations. Half of all women reported using medications for terminating pregnancies and the number of hospital admissions due to complications from abortion decreased from 1992 to 2009. Maternal morbimortality from abortion had a reduced frequency but it is likely that maternal deaths from abortion are under-reported. Conclusions: Abortion is frequently used in Brazil, especially in less-developed regions and by more socially-vulnerable women. Access to safer methods probably contributed to the reduction of complications, hospitalizations and morbimortality from abortion. However, half of all women still used other unsafe methods and the number of admissions due to complications from abortion is still high. The small scientific production and lack of methodological adequacy led to the development of a special issue on Abortion in Brazil in the jornal Reports in Public Health. Key messages: Restrictive legislation does not prevent abortion, but limits access to safe abortion and makes it diffiult to prevent morbidity and mortaliity from abortion. Restrictive legislation and the stigma associated with abortion make studies difficult to estimate the rates, complications and factors associated with abortion.